Network structure and local adaptation in co‐evolving bacteria–phage interactions. Issue 7 (6th February 2017) - Gurney, James; Aldakak, Lafi; Betts, Alex; Gougat‐Barbera, Claire; Poisot, Timothée; Kaltz, Oliver; Hochberg, Michael E.
Abstract: Numerous theoretical and experimental studies have investigated antagonistic co‐evolution between parasites and their hosts. Although experimental tests of theory from a range of biological systems are largely concordant regarding the influence of several driving processes, we know little as to how mechanisms acting at the smallest scales (individual molecular and phenotypic changes) may result in the emergence of structures at larger scales, such as co‐evolutionary dynamics and local adaptation. We capitalized on methods commonly employed in community ecology to quantify how the structure of community interaction matrices, so‐called bipartite networks, reflected observed co‐evolutionary dynamics, and how phages from these communities may or may not have adapted locally to their bacterial hosts. We found a consistent nested network structure for two phage types, one previously demonstrated to exhibit arms race co‐evolutionary dynamics and the other fluctuating co‐evolutionary dynamics. Both phages increased their host ranges through evolutionary time, but we found no evidence for a trade‐off with impact on bacteria. Finally, only bacteria from the arms race phage showed local adaptation, and we provide preliminary evidence that these bacteria underwent (sometimes different) molecular changes in the wzy gene associated with the LPS receptor, while bacteria co‐evolving with the fluctuating selection phage did not show local adaptation and had partial deletions of the pilF gene associated with type IV pili. We conclude that the structure of phage–bacteria interaction networks is not necessarily specific to co‐evolutionary dynamics, and discuss hypotheses for why only one of the two phages was, nevertheless, locally adapted.